2020
DOI: 10.1016/j.coelec.2020.04.009
|View full text |Cite
|
Sign up to set email alerts
|

3D-printed electrochemical sensors: A new horizon for measurement of biomolecules

Abstract: Electrochemical sensors are widely used to monitor biomolecules. However, limitations in sensor geometry has restricted the scope of currently utilised electrochemical sensors. 3D-printing has emerged as a promising manufacturing approach, to robustly make electrochemical sensors, that can stably measure in biological environments. This review highlights the recent trends in the development of 3D-printed electrodes and biosensors for measurement of biomolecules. Novel geometries of 3D-printed electrodes have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…Three-dimensional (3D) fused filament fabrication (FFF) printing has emerged as an important manufacturing approach for the development of conductive carbon materials, mainly in the fields of electronics, sensors and energy storage devices as it offers flexibility in design and potential that supersedes traditional manufacturing systems. [1][2][3][4][5][6] Studies have shown that commercial conductive carbon 3D-printed filament has poor conductivity. [7][8][9][10] To overcome these limitations, varying postprinting modifications have been utilised in order to enhance the electrical properties of the 3D-printed material, such as chemical and electrochemical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) fused filament fabrication (FFF) printing has emerged as an important manufacturing approach for the development of conductive carbon materials, mainly in the fields of electronics, sensors and energy storage devices as it offers flexibility in design and potential that supersedes traditional manufacturing systems. [1][2][3][4][5][6] Studies have shown that commercial conductive carbon 3D-printed filament has poor conductivity. [7][8][9][10] To overcome these limitations, varying postprinting modifications have been utilised in order to enhance the electrical properties of the 3D-printed material, such as chemical and electrochemical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Surface engineering has been responsible to light up different nanocomposites made of both inorganic and organic components for their custom application in extremely divers fields. [1,2,3,4,5] Particularly, the use of functional inorganic nanoparticles (FINPs) has received considerable attention owing to their catalytic and electrochemical features, providing great and polylactic acid (PLA) are being extensively used for several electrochemical applications, including electroanalysis, [28,29,30,31] energy (storage and conversion) [32,33,34,35] and switching memories. [36] However, a main limitation when using 3D-nCEs can be clearly identified: the lack of effective (bio)functionalization methods for tuning their functional capabilities, being mainly limited to the use of weak physisorption or costly sputtering processes.…”
Section: Introductionmentioning
confidence: 99%
“…Fused deposition modeling (FDM) is an innovative 3D printing process in which a sensor is CAD designed and then printed from thermoplastic filaments by a 3D printer. This digital process requires low-cost and desktop-sized printers and it provides ease of operation by non-trained handlers, design flexibility and transferability via e-mail, while it produces eco-friendly and disposable sensors [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%